Stabilization of residual soil with rice husk ash and cement - Basha, E.A.; Hashim, Roslan; Mahmud, H.B.; Muntohar, A.S. (Elsevier, 2005)
Stabilization of residual soils is studied by chemically using cement and rice husk ash. Investigation includes the evaluation of such properties of the soil as compaction, strength, and X-ray diffraction. Test results show that both cement and rice husk ash reduce the plasticity of soils. In term of compactability, addition of rice husk ash and cement decreases the maximum dry density and increases the optimum moisture content. From the viewpoint of plasticity, compaction and strength characteristics, and economy, addition of 6-8 cement and 10-15 rice husk ash is recommended as an optimum amount.